Improving The Methodological Problems of Determining the Level of Importance in Auditing Inspections - N. Xasanova (Research Parks Publishers, 2022)
This article examines the methodological basis for determining the level of materiality in audit firms and identifies problems in this area, as well as measures to eliminate and improve them.